Inclusion of universal design towards user-centric interior design process in Malaysia - Mansor, Noranita (2017)
Misinterpretation on the “real user” in interior design becomes a fundamental issue that prohibits interior designers to include new design thinking in the interior design process. The purpose of this research is to strategize on how to include Universal Design (UD) is a common practice in interior design process towards users centric in Malaysia. This study uses literature survey in comprehend UD theories and practice. The results from the literature survey assist this research in generating a theoretical proposition. In order to answer the main research question, this research employs case study research methodology in two phases. The first phase is to examine the compliances of Malaysia standard 1184:2014 (UD and accessibility in the built environment-code of practice (second revision) in built environment in Malaysia. The second phase is to document the current interior design process practices in Malaysia. The results from the first phase established that most of the selected building samples in this study moderately comply the MS 1184:2014. The findings give an evidence for this study to strategize for included UD in the interior design process. As a final, the second phase of data collection on documentation of the current interior design process in Malaysia has been performed. The results had been streamlined into twelve best interior design task descriptions. The streamlining design tasks contribute for this study to propose a potential stage for include UD in the interior design process. There are seven potential stages for UD inclusion in Interior design process. Then, this study recommends the inclusion of UD in the interior design process through the theoretical model in demonstrating the theoretical proposition of this study which posits “designers can successfully include UD by introducing empathic comprehension about all users have restricted capabilities during the conventional design process”. The recommendations are expected to be benefits for interior designers to stay relevant in design practice especially in designing toward users centric and to support demographic change issue related to interior design in Malaysia.